Clinical Characteristics and Treatment Outcomes of Scleromyxedema: A 10-Year Retrospective Survey - Abtin Ansari; Zohre Erfani; Maryam Daneshpazhooh; Leila Mahmoudi; Zahra Saffarian; Kambiz Kamyab; Hamidreza Mahmoudi (Karger Publishers, 2022)
Scleromyxedema is a rare but important mucinosis disorder of the skin that is presented with dermatological manifestations such as waxy papules, diffuse induration, and nondermatologic involvements like neurological and renal disorders. We report a case series of the data regarding the characteristics and treatment of 14 patients diagnosed with scleromyxedema and their follow-up. Patients entered the study based on scleromyxedema diagnosis criteria. Comorbidities were also recorded to evaluate their effect on the treatment process. Clinicopathological and laboratory findings and responses to their treatment were evaluated separately. There was a significant improvement after administering intravenous immunoglobulin (IVIG). Despite the lack of a definite treatment for this condition, the present study shows that the application of IVIG can improve both cutaneous and systemic symptoms. Younger patients, in particular, responded significantly to the use of IVIG. More studies are required to investigate the potential efficacy of IVIG in the treatment of scleromyxedema.